68 Effects of Plant Growth-Promoting Rhizobacteria on Fall-Stockpiled Bermudagrass. (28th November 2020) - Cole, Madison; Griffin, Megan E; Dillard, Sandra L; Mullenix, Mary K; Muntifering, Russ B; Held, David
Abstract: Forage production practices have been greatly affected by the increasing cost of N fertilization. Therefore, supplemental and alternative N sources are needed to ensure the economic viability of these systems. A 2-yr, small plot study was designed to evaluate plant growth-promoting rhizobacteria (PGPR) as an alternative form of N fertilizer for fall-stockpiled bermudagrass (Cynodon dactylon). Eighteen 1-m 2 'Coastal' bermudagrass plots were treated with a synthetic N fertilizer, DH44 (PGPR strain), DH44+fertilizer, Blend 20 (PGPR blend), Blend 20+fertilizer, and a control, then stockpiled through the fall. Two PGPR applications were applied in late-August and again 30 d later. Fertilizer and PGPR+fertilizer plots received (NH4 )2 SO4, at a rate of 56 kg N/ha. One-third of each plot was clipped to 2.5 cm in November, December, and January, respectively. Forage DM yield, CP, NDF, ADF, and ADL were determined via wet chemistry at the Auburn University Ruminant Nutrition Laboratory (Auburn, AL). Data were analyzed using PROC MIXED (SAS 9.4, SAS Inst., Cary, NC) as a completely randomized design. Yield was greatest (P ≤ 0.0318) for Blend 20+fertilizer, but it was not different (P = 0.2552) from that of the synthetic fertilizer (1, 914 kg ha -1, 1, 768 kg ha -1, respectively). Concentration of CP was least (P ≤ 0.0437) for DH44 and Blend 20 treatments (90 g kg -1 and 92 g kg -1, respectively). Concentrations of NDF for the control were different (P ≤ 0.0045) for all treatments except synthetic fertilizer (P = 0.1092). Concentrations of ADF were not different (P ≥ 0.1613) excluding the control (P ≤ 0.0525; 342.8 g kg -1 and 358.0 g kg -1, respectively). In vitro true digestibility (IVTD) was not different (P = 0.0947) among all treatments (463.1 g kg -1 ). All yield and nutritive value parameters were greater (P ≤ 0.0246) in Year 2. These results indicate that PGPR is a viable option for biofertilization of fall-stockpiled bermudagrass; however, further investigation into the effects of PGPR inoculants at a field scale are needed.